KAP study of bio-medical waste management among health care workers in Delhi - Soyam, Gajanan C.; Hiwarkar, Prabhakar A.; Kawalkar, Umesh G.; Soyam, Vishal C.; Gupta, Vimal K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Bio-medical waste management is vital issue not only to hospitals, but also to the environment, law enforcement agency, media and to the general public.The objectives of the study were to find out level of knowledge, attitude and practices of health care workers (HCWs) about bio-medical waste management in a rural hospital of Delhi. Methods: A cross sectional study was carried out in rural hospital, Delhi on 155 HCWs. Pre-designed, pretested, structured questionnaire were administered on 155 HCWs of hospital. Data collected and analyzed by using SPSS-17. Results: Total of 155 HCWs were selected. Majority of HCWs were in the age group of 30.3 years±5.6 (mean age±SD) Almost half (54.2%) of study population comprised of female. Most of them were nursing staff. Mean years of experience in service was 4.8±3.7 (mean age±SD). Majority HCWs in this study took education up to senior secondary and they possess respective professional qualification. Statistically significant numbers of HCWs vaccinated with HBV vaccine and received training of bio-medical waste management (p<0.05). Almost all (97.4%) HCWs aware of bio-medical waste management rules and have very positive attitude. Practice of HCWs regarding bio-medical waste management was relatively poor. Conclusions: Nursing staff have not only best knowledge and attitude but also good practices among all HCWs. Additional training have been required to Paramedics and group-D workers.